2017
DOI: 10.1002/btpr.2445
|View full text |Cite
|
Sign up to set email alerts
|

Control of chitin nanofiber production by the lipid‐producing diatom Cyclotella Sp. through fed‐batch addition of dissolved silicon and nitrate in a bubble‐column photobioreactor

Abstract: Diatoms are single-celled algae that make cell walls of nanopatterned biogenic silica called frustules through metabolic uptake of dissolved silicon and its templated condensation into biosilica. The centric marine diatom Cyclotella sp. also produces intracellular lipids and the valued coproduct chitin, an N-acetyl glucosamine biopolymer that is extruded from selected frustule pores as pure nanofibers. The goal of this study was to develop a nutrient feeding strategy to control the production of chitin nanofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Increased chitin production could strengthen the cell wall in response to increased intracellular turgor pressure. Extracellular chitin threads also promote increased buoyancy in the water column (Chiriboga & Rorrer, 2017; Morin et al, 1986). This might help diatoms optimize environmental light and temperature conditions (Boyd & Gradmann, 2002; Falciatore et al, 2000; Falciatore & Bowler, 2002), so one hypothesis is that diatoms also regulate buoyancy in response to salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…Increased chitin production could strengthen the cell wall in response to increased intracellular turgor pressure. Extracellular chitin threads also promote increased buoyancy in the water column (Chiriboga & Rorrer, 2017; Morin et al, 1986). This might help diatoms optimize environmental light and temperature conditions (Boyd & Gradmann, 2002; Falciatore et al, 2000; Falciatore & Bowler, 2002), so one hypothesis is that diatoms also regulate buoyancy in response to salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…Another very interesting example of the application of diatoms cells as living biofactories was provided in 2017 by Chirinboga and Rorrer . The two algal species Cyclotella and Thalassiosira have the specific ability of producing chitin, the N‐acetyl glucosamine biopolymer with biomedical properties, which is extruded from the diatom cell as rigid microfibrils with a diameter of 50 nm and high purity in the β‐crystalline form.…”
Section: In Vivo Modification Of Biosilica Shellsmentioning
confidence: 99%
“…Chitin fibers are shown emanating from pores lining frustule valve rim. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: In Vivo Modification Of Biosilica Shellsmentioning
confidence: 99%
“…The cell surface chemistry plays a vital role in NP production since the cell surface adsorption-reduction of metal cations contributes more to NP synthesis than intracellular NP formation following the metal uptake [ 12 ]. Many studies have reported the cell surface involvement in the production of NPs, as presented in Table 1 [ 72 , 73 , 74 , 75 , 76 , 77 ]. The negatively charged surface groups of the cells, such as hydroxyl, carboxyl, and phosphate, have an affinity for metal cations [ 78 , 79 ].…”
Section: In Vivo Biosynthesis Of Inorganic Nanomaterials Using LIVmentioning
confidence: 99%